THERMODYNAMIC ASSESSMENT OF LIF-NAF-KF-UF-4 SYSTEM - Akmal Muzakki, Naufal
Nuclear power plays an important role in addressing climate change and in enabling energy transition from fossil fuels to renewable powers. The development of nuclear reactor has come up to the utilization of molten salts, either as coolant and even as part of reactor fuel mixture. The purpose of this research is to study the salt chemical and the melting behavior of a relevant Molten Salt Reactor (MSR) fuel system, which is LiF-NaF-KF-UF4 system through thermodynamic simulation.